Enhancing Online Assessment Quality in Higher Education: The Design of Moodle Plug-in for Personalised Exam Revision (PER) - Smahi, Kaoutar; Labouidya, Ouidad; El Khadiri, Khalid (International Journal of Engineering Pedagogy (iJEP), 2025)
The diversity of learner profiles in online environments underlines more than ever the importance of a personalised approach to effectively addressing assessment and revision needs for exams to ensure better adaptation to individual needs, enhance the learning experience and maximise learners’ chances of success. MOODLE (modular object-oriented dynamic learning environment), a leading learning management platform (LMS), supports a number of activities for the assessment of learning. Unfortunately, there is currently no module designed for personalised revision. The personalised exam revision (PER) plug-in for MOODLE is intended to enhance the personalisation of revision for examinations. This work explores the process of designing and developing an adaptive plug-in for MOODLE, designed to enhance the personalisation of learning paths. Based on the ADDIE (analysis, design, development, implementation, and evaluation) methodology, this study begins with an analysis of the needs of the main users, putting the learner at the centre of interest. This study identified opportunities for integration and optimisation, highlighted current strengths and weaknesses, and reinforced our positioning concerning the literature and the revision path outlined in our specification. By combining a proven methodology with a learner-centred approach, the ultimate goal is to offer learners and teachers a complete, powerful assistant for enriching, personalising and monitoring online revision.